INOVASI APLIKASI MOBILE BERBASIS KECERDASAN BUATAN PADA LAYANAN DINAS SOSIAL PROVINSI JAWA TIMUR MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Kandhi Surya Atmadja (Prosiding Seminar Nasional Indonesia, 2026)
Delivering public services and social aid frequently faces hurdles regarding data precision and information access. This research focuses on the creation of a React Native-based mobile app prototype equipped with an AI chatbot, functioning as a digital information hub for the East Java Provincial Social Services. The study utilizes the Rapid Application Development (RAD) methodology, encompassing Requirements Planning, User Design (UI/UX with Figma), Construction (frontend with React Native, backend via Supabase, and AI training), and Cutover phases. This rapid iterative process produces the E-JSC application, a versatile platform featuring an AI chatbot ("Tanya JSC"), social aid transparency dashboards ("SapaBansos"), and online permit services. By incorporating Artificial Intelligence, the system autonomously handles frequent public questions, thereby minimizing queues at service centers. Ultimately, this mobile solution effectively upgrades public service operations, guaranteeing that social aid details remain precise, reachable, and well-managed.